2012
DOI: 10.5586/aa.2012.030
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intercropping carrot (Daucus carota L.) with french marigold (Tagetes patula nana L.) and pot marigold (Calendula officinalis L.) on the occurrence of some pests and quality of carrot yield

Abstract: A b s t r a c tIntercropping combines different aspects of the interaction between organisms in ecosystems and may be classified as a pro-ecological method of plant cultivation limiting the harmful human interference in the environment, especially the use of chemicals. It also allows high yield, good quality, and economic productivity to be achieved. The aim of the present study, conducted in the years [2003][2004] in Mydlniki near Kraków, was to determine the effect of intercropping carrot Nardin F 1 with Fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 12 publications
2
5
0
Order By: Relevance
“…Several studies on the effect of intercropping in the management of insects have been described in the literature and the results were similar to those found in this work [14][15][16][17][18][19][20][21].…”
Section: Discussionsupporting
confidence: 80%
“…Several studies on the effect of intercropping in the management of insects have been described in the literature and the results were similar to those found in this work [14][15][16][17][18][19][20][21].…”
Section: Discussionsupporting
confidence: 80%
“…This study agreed with that of Hussain and Bilal (2007) that the highest fruit damaged was from sole cropping of tomato as compared to tomato-marigold intercropping. Similar Jankowska et al (2012) that the highest unmarketable yield of carrot was obtained from sole cropping but the lowest from carrot-marigold intercropping. Because intercropping of marigold with carrot enables to protect insect pests and other soil born nematodes by its flower and root system, respectively.…”
Section: Unmarketable Fruit Yieldsupporting
confidence: 72%
“…Both carotenoids and chlorophylls are largely influenced by genetic variation and growing conditions. Previous studies revealed an impact of intercropping on carotenoids as well as chlorophylls in various crops, e.g., amaranth leaves ( Ng’ang’a et al, 2009 ), carrots ( Jankowska et al, 2012 ), Chinese cabbage ( Cai et al, 2011 ) , and Moringa ( Abou-Zeid and Salama, 2014 ). In our study the intercropping did not significantly change the concentration of the photosynthetic pigments, whereas the water supply impacted their concentration.…”
Section: Discussionmentioning
confidence: 99%